Insight Into the Multiple Branches Traits of a Mutant in Larix olgensis by Morphological, Cytological, and Transcriptional Analyses - Cai, Kewei; Zhou, Xueyan; Li, Xiang; Kang, Ye; Yang, Xiaoming; Cui, Yonghong; Li, Guangyan; Pei, Xiaona; Zhao, Xiyang (Frontiers in Plant Science, 2021)
Larix olgensis is a tall deciduous tree species that has many applications in the wood fiber industry. Bud mutations are somatic mutations in plants and are considered an ideal material to identify and describe the molecular mechanism of plant mutation. However, the molecular regulatory mechanisms of bud mutations in L. olgensis remain unknown. In this study, dwarfed (or stunted), short-leaved and multi-branched mutants of L. olgensis were found and utilized to identify crucial genes and regulatory networks controlling the multiple branch structure of L. olgensis. The physiological data showed that the branch number, bud number, fresh and dry weight, tracheid length, tracheid length–width ratio, inner tracheid diameter, and epidermal cell area of mutant plants were higher than that of wildtype plants. Hormone concentration measurements found that auxin, gibberellin, and abscisic acid in the mutant leaves were higher than that in wildtype plants. Moreover, the transcriptome sequencing of all samples using the Illumina Hiseq sequencing platform. Transcriptome analysis identified respectively 632, 157 and 199 differentially expressed genes (DEGs) in buds, leaves and stems between mutant plants and wildtype. DEGs were found to be involved in cell division and differentiation, shoot apical meristem activity, plant hormone biosynthesis, and sugar metabolism. Furthermore, bZIP, WRKY, and AP2/ERF family transcription factors play a role in bud formation. This study provides new insights into the molecular mechanisms of L. olgensis bud and branch formation and establishes a fundamental understanding of the breeding of new varieties in L. olgensis.